Phonetic encoding for Bangla and its application to spelling checker , transliteration , cross language information retrieval and name searching - Naushad UzZaman (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2005.